In Valéry ’s "poiesis", the vertigo of the digit, memory and forgetfulness - Vieira da Cunha, Eduardo (PORTO ARTE: Revista de Artes Visuais, 2013)
The article presents a parallel between the processes of making art based on Paul Valéry’s poiesis, and attempts to establish a parallel between the digital models of decomposition and unfolding of the digital image and the weaves of simultaneous elements that occur in the process of making art. It seeks, in the dialectic relation between memory and forgetfulness, gaps and holes to deal with a process of artistic mutation.